Using Instructional Design, Analyze, Design, Develop, Implement, and Evaluate, to Develop e-Learning Modules to Disseminate Supported Employment for Community Behavioral Health Treatment Programs in New York State - Patel, Sapana R.; Margolies, Paul J.; Covell, Nancy H.; Lipscomb, Cristine; Dixon, Lisa B. (Frontiers in Public Health, 2018)
Background: Implementation science lacks a systematic approach to the development of learning strategies for online training in EBPs that takes the context of real-world practice into account. The field of instructional design offers ecologically valid and systematic processes to develop learning strategies for workforce development and performance support. Objective: This report describes the application of an instructional design framework - Analyze, Design, Develop, Implement, and Evaluate (ADDIE) model- in the development and evaluation of e-Learning modules as one strategy among a multifaceted approach to the implementation of Individual Placement and Support (IPS), a model of supported employment for community behavioral health treatment programs, in New York State. Methods: We applied quantitative and qualitative methods to develop and evaluate three IPS e-Learning modules. Throughout the ADDIE process, we conducted formative and summative evaluations. Formative evaluations consisted of qualitative feedback received from recipients and providers during early pilot work, which identified training and implementation support needs. The summative evaluation consisted of levels 1 and 2 (reaction to the training, self-reported knowledge and practice change) quantitative and qualitative data and was guided by the Kirkpatrick model for training evaluation. Results: Learners received the e-learning modules favorably, rating them highly overall and noting that they met stated learning objectives. learners self-report of knowledge acquisition was high (mean range: 4.4-4.6 out of 5). About half of learners indicated that they would change their practice after watching the modules (range: 48%-51%). All learners who completed the Level 1 evaluation demonstrated 80% or better mastery of knowledge on the Level 2 evaluation embedded in each module. Conclusions: Instructional design approaches such as ADDIE may offer implementation scientists and practitioners a flexible and systematic guideline for the development of e-Learning modules as a single component or one strategy in a multifaceted approach for training practitioners in EBPs.